SISTEM INFORMASI UJIAN AKHIR SEMESTER PADA MTSM MUARA PANAS MENGGUNAKAN BAHASA PEMOGRAMAN JAVA - Dinda Arista Ramadhani; Jeprimansyah, Jeprimansyah; Reti Handayani; Etika Melsyah Putri (Yayasan Nusantara Hasana Berdikari, 2025)
The final examination information system (UAS) is an important component in the field of education that functions to efficiently manage and process examination data. This study aims to design and implement a UAS information system at MTsM Muara Panas using the Java programming language. The method used in the development of this system is the Waterfall method, which consists of the stages of analysis, design, implementation, and testing.The developed system allows for the management of student data, examination scheduling, and the automatic assessment of examination results. By using Java as the programming language, this system is expected to provide a user-friendly interface and optimal performance. The results of this study indicate that the developed UAS information system can enhance the efficiency of examination management, reduce errors in grading, and facilitate access to information for both students and teachers.